Achieving customer satisfaction through service and product excellence - Nur Asiah; Wuchi Wulandari Azzahra; Umban Adi Jaya (Faculty of Economics and Business Mulawarman University, 2023)
So far, customer satisfaction is still a major issue and concern for BTPN Syariah to survive in the intense competition among sharia banks in Indonesia. The bank strives to provide the best service and offer better quality products than competing banks. This study intends to determine the impact of service and product excellence on customer satisfaction. The study employed a quantitative approach and data collection using questionnaires distributed to 237 BTPN Syariah MMS Haurwangi Cianjur customers. Data analysis and hypothesis testing were carried out by regression analysis using SPSS. This study found that service and product excellence had a positive impact on customer satisfaction. The staffs were able to communicate well and explain the products in detail and clearly. BTPN Syariah financing was very useful for customers' business capital. In terms of service, customers highlighted the responsiveness and assurance of Banks in serving customers. In terms of product, Banks need to keep up to date with customer needs and reward loyal customers. Respondents in this study were rural communities with the majority not having a high level of education. The results are expected to add insight into the literature and banks concern. Future researchers can develop more in-depth research.